Characterization of silver diamine fluoride cytotoxicity using microfluidic tooth-on-a-chip and gingival equivalents. Issue 8 (August 2022) - Hu, Shijia; Muniraj, Giridharan; Mishra, Apurva; Hong, Kanglun; Lum, Jing Li; Hong, Catherine Hsu Ling; Rosa, Vinicius; Sriram, Gopu
Abstract: Objective: This study aims to characterize the cytotoxicity potential of silver diamine fluoride (SDF) on dental pulp stem cells (DPSC) and gingival equivalents. Methods: DPSC cultured on 96-well plates was exposed directly to SDF (0.0001–0.01%) and cell viability (IC50 ) quantified. Effect of SDF on DPSC viability under flow (with dentin barrier) conditions was evaluated using a custom-designed microfluidic "tooth-on-a-chip". Permeability of dentin discs (0.5–1.5 mm thickness) was evaluated using lucifer yellow permeation assay. Dentin discs were treated with 38% SDF (up to 3 h), and cell viability (live/dead assay) of the DPSC cultured in the inlet (unexposed) and outlet (exposed) regions of the pulp channel was evaluated. To assess the mucosal corrosion potential, gingival equivalents were treated with 38% SDF for 3 or 60 min (OECD test guideline 431) and characterized by MTT assay and histomorphometric analysis. Results: DPSC exposed directly to SDF showed a dose-dependent reduction in cell viability (IC50 : 0.001%). Inlet channels (internal control) of the tooth-on-a-chip exposed to PBS and SDF-exposed dentin discs showed> 85% DPSC viability. In contrast, the outlet channels of SDF-exposed dentin discs showed a decreased viability of< 31% and 0% (1.5 and ≤1.0 mm thick dentin disc, respectively) (p < 0.01). The gingiva equivalents treated with SDF for 3 and 60 min demonstrated decreased epithelial integrity, loss of intercellular cohesion and corneal layer detachment with significant reduction in intact epithelial thickness (p < 0.05). Significance: SDF penetrated the dentin (≤1 mm thick) inducing significant death of the pulp cells. SDF also disrupted gingival epithelial integrity resulting in mucosal corrosion. Highlights: Silver diamine fluoride (SDF) was toxic to dental pulp stem cells even at low concentrations (<0.001%). SDF can be classified as corrosive (sub-category 1 A) to human gingiva. SDF penetrated 1 mm-thick sound dentin slices, causing dental pulp stem cell death. Clinical studies are needed to evaluate SDF toxicity potential in deep carious lesions.